An Economic Perspective on Environmental Regulation - Freeman, A. (Maine Policy Review, 1992)
The laws and regulations that govern the use of environmental resources have complicated effects on our society and our economy. Efforts to regulate environmental impacts are frequently controversial precisely because they have such complicated effects. No single perspective can adequately encompass all of the issues that arise in environmental regulation and environmental protection. Even the terms themselves suggest the fundamentally opposed philosophies that approach the assessment of environmental laws: While proponents of greater environmental activism emphasize the need to "protect" the environment, critics of more stringent controls emphasize that these laws "regulate" and limit the actions of individuals. At the PURE '92 conference, speakers with very different perspectives were invited to share their views of the important issues in environmental protection and environmental regulation. Myrick Freeman provides an economic perspective.
Keywords: environmental protection; environmental regulation